The unfinished book - Gillespie, Alexandra ca. 20./21. Jh; Lynch, Deidre 1961- (Oxford twenty-first century approaches to literature, 2021)
Assessing a wide variety of particular books, book-like objects, and book collections, and working with millennia of variable and conflicting definitions of the book and its purposes, The Unfinished Book surveys the many things that books have been, and uncovers why the book's grip on the cultural imagination remains so tenacious